Takotsubo Syndrome (TTS) in Onco-Hematologic Patients: Retrospective Analysis and Focus on the Correlation or Not With Anticancer Drugs. Case Reports and Review of the Literature - Monti, Manlio; Cortesi, Pietro; Vespignani, Roberto; Bronico, Ilaria; Gallio, Chiara; Flospergher, Michele; Matteucci, Laura; Frassineti, Giovanni Luca (Frontiers in Oncology, 2022)
Takotsubo syndrome (TTS) is an uncommon cardiovascular condition also known as stress-induced cardiomyopathy or broken heart disease. The syndrome, characterized by acute non-coronary segmental ventricular dysfunction, commonly occurs as a reaction to severe emotional or physical stress and can cause significant problems. Several classes of chemotherapeutic agents that are known to be cardiotoxic have been shown to be associated with TTS in cancer patients. Describing a case of TTS from chemotherapy and/or monoclonal antibody is important because these drugs are widely used and their temporary or permanent suspension could compromise the success of treatment. The detection and reporting of suspected adverse drug reactions in clinical practice are the foundations of postmarketing surveillance. We performed a retrospective analysis of a large number of patients followed at our cancer centre to identify drugs that could lead to the onset of TTS, focusing our attention on 2 monoclonal antibodies, bevacizumab and rituximab plus chemotherapy. A search was carried out for the word “Takotsubo” in database sources such as in PubMed, in medical oncology, radiology and cardiology electronic clinical records. From October 2007 to March 2021, of the 79,005 patients seen or treated for any kind of malignancy at our institute, 9 had a diagnosis of TTS (4 before and 5 after the diagnosis of malignancy). Only 2 patients had TTS after treatment with the anticancer drugs, bevacizumab and rituximab plus chemotherapy. These two patients were hospitalised, one for subocclusion while the other for pulmonary embolism (PE) with a life threatening condition and in need of intravenous catecholamines. For both patients, an ECG, echocardiography and coronary angiography were performed as well as blood tests with a subsequent diagnosis of TTS and both received cardiological treatment with resolution of the clinical picture. A reassessment of the two cases found that a subocclusion and intravenous catecholamines appeared to be the most likely triggers. In conclusion, TTS is rare in cancer patients. Identifying TTS triggers could be useful because it could induce therapeutic changes.